PRIMARY VAGINAL MELANOMA - conic, irena; Conic, Irena; Stojnev, Slavica; Petkovic, Ivan; Krtinic, Dane; Milovic Kovacevic, Marijana (Acta medicae Medianae, 2026)
Primary vaginal melanoma is a rare type of mucosal melanoma accounting for 0.3% to 0.8% of all melanomas in women and less than 3% of all vaginal malignancies. A 78-year-old female presented with complaints of vaginal tingling, vaginal watery vaginal discharge, and dysuria lasting for four months, with a gradual increase in symptom frequency over time. The patient underwent complete tumor excision. Immunohistochemical analysis showed that the tumor cells were strongly positive for SOX10, HMB-45, and S100 proteins. Histopathological examination of the entire tumor revealed epithelioid melanoma cells in the vertical (invasive) growth phase with no evidence of a preceding radial growth phase. Most tumor cells contained dark-brown intracellular pigment. Superficial microscopic ulceration was present. The Breslow tumor thickness was 12 mm. Tumor-infiltrating lymphocytes were non-brisk, and the mitotic rate was 15 mitoses per mm2. Lymphovascular invasion was present, while perineural and intraneural infiltration were not noticed. Tumor regression and microscopic satellites were absent. The deep resection margin was free of tumor cells. According to the AJCC 8th edition melanoma staging system, the tumor was classified as stage IIC (T4b, N0, M0). Surgical resection with wide local excision remains the mainstay in the treatment of this aggressive disease with poor overall survival. Mucosal melanoma arising in the vaginal wall is often clinically indiscernible; therefore, prompt biopsy and timely, accurate diagnosis are of crucial importance.